APLIKASI ABSENSI KERJA LEMBUR KARYAWAN BERBASIS CLOUD COMPUTING SEBAGAI SOFTWARE AS A SERVICE (SAAS) - Martilinda Panjaitan; Agustin Agustin; Herwin Herwin; M. Khairul Anam (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
Rista Lamtama Engineering is a Riau Andalan Pulp and Paper contractor company engaged in project services. Consisting of 136 employees, the processing of overtime attendance data for the company Rista Lamtama Engineering is still carried out conventionally, namely recapping the overtime attendance data one by one and then processing it using Microsoft Excel. This method is not efficient and effective in terms of time and effort. Employees who work overtime in the field experience difficulties in attending to the office. An attendance system like this creates fraud when filling in attendance in the form of entrusted absences, even though they don't come overtime, causing misunderstandings between employees and the office and can be detrimental to PT. Overcoming this problem, an attendance application was created by utilizing cloud computing with software as a service (SaaS) services. The existence of cloud computing technology allows data access from anywhere and using a fixed or mobile device. The system built can help the company Rista Lamtama Engineering in managing employee overtime data, a system created using cloud computing is also more effective in storing data on employees who work overtime and reduces employee fraud in absenteeism overtime because of the location when employees attend attendance can be seen. The system built for Android Studio-based employee overtime attendance applications. All available features are running well and judging from the tests that have been carried out with compatibility testing, blackbox testing,and usability testing, it can be concluded that the system built has met the needs of employees of PT. Rista Lamtama Engineering, for its own cloud computing, utilizes the firebase database firestore where all employee data that has performed overtime attendance has been successfully stored in the firebase database firestore.